AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING RECOUNT TEXTS - Vikri Februansyah; Irsyad Nugraha; Yustika Nur Fajriah (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
This study is aimed at investigating students’ difficulties in writing recount text. To achieve that purpose, qualitative approach embracing case study design was used in this study. The data were taken from eight texts of the third graders in one of Universities at Garut. The data were then analyzed using the genre rubric from Knapp and Watkins (2005). The result reveals that students are still difficult in organizing the structure of recount text and delivering ideas through the correct grammar such as conjunction, past tense, and mental verb